Pulmonary recurrence in patients with endometrial cancer. Issue 4 (April 2016) - Turan, Taner; Ureyen, Isin; Karalok, Alper; Tasci, Tolga; Turkmen, Osman; Kocak, Ozgur; Koc, Sevgi; Tulunay, Gokhan
Abstract : Background : In this article, we aimed to define the clinical, pathological, and surgical factors predicting pulmonary recurrence (PR) and determining survival after PR in patients with endometrial cancer. Methods : Thirty‐six (2.7%) patients were analyzed who suffered pulmonary failure in the first recurrence out of 1345 patients who had at least extrafascial hysterectomy plus bilateral salpingo‐oophorectomy for endometrial cancer between January 1993 and May 2013. The recurrence was designated as an isolated PR in cases of the presence of recurrence only in the lung, while it was called a synchronized PR if the patient had extrapulmonary recurrence in addition to PR. Results : In the multivariate analysis in the entire cohort, only International Federation of Gynecology and Obstetrics stage was an independent prognostic factor for PR. Two‐year overall survival (OS) was 52% in patients with PR. In the univariate analysis, early International Federation of Gynecology and Obstetrics stage, absence of lymphatic metastasis, negative lymphovascular space invasion, absence of cervical invasion, negative adnexal spread, negative peritoneal cytology, negative omental metastasis, adjuvant radiotherapy after initial surgery, isolated PR, and chemotherapy upon recurrence were associated with improved OS after PR. The OS was 54 months for patients with isolated PR, while it was 10 months for patients who had synchronized PR. Furthermore, OS was 43 months and 13 months for the patients who took chemotherapy and radiotherapy, respectively. Conclusion : Advanced stage is associated with PR. If recurrence is only in the lung, survival is better. Systemic treatment after PR is associated with improved survival. However, multi‐center studies are required to standardize the treatment for PR.